The Application of The Use Integration Technique in Solving An Integral Problem - Sri Rejeki Dwi Putranti (Alliance of Health Activists (AloHA), 2020)
There are many integration techniques that can be used to solve an integral problem.In this material, several integration techniques will be discussed including substitution, the properties of algebra and trigonometry and techniques commonly used in test books.If we are faced with integral problems that cannot be solved by techniques ,what we have learned, we use partial integral techniques. Partial integration technique is obtained by integrating the derivative formula of the product by two functions. Keywords: integration technique; substitution; partial integration technique